Determinação de difusividade térmica de ferramentas de corte revestidas via técnica fotoacústica de célula aberta - Barboza, Tialin (2018)
Machining is one of the most widely used manufacturing processes in the world. It consists of the removal of material through the contact between a cutting tool and the part to be machined. Such contact generates large amounts of heat, requiring a refrigerant fluid to remove this heat. However, such a fluid has proved detrimental when taken into account environmental issues. In this way, improvements have been made to perform the dry machining, that is, without the use of refrigerant fluids. For such advances to be possible, it is necessary to study the thermal properties of cutting tools. The present work performs the thermal diffusivity measurement using open photoacoustic cell technique of hardmetal cutting tool coatings. Two samples from different manufacturers named X and Y were analyzed. The X-sample coatting had a thermal diffusivity of (0.62 cm² / s +/- 0.08) cm² / s. On the other hand, the value for the thermal diffusivity of the Y-sample coating was shown to be undetermined because the thickness of this layer was thiner. In addition, it was possible to differentiate the heat propagation between the samples by analyzing the chemical composition of the coatings using scanning electron microscopy, as well as the hardness of the substrate and the coating by nanoidentation.